A guide, cornerstone, and appetizer: An elicited metaphor analysis of Chinese university students' perceptions of English language textbooks. - Molly Xie Pan; Wei Lin (PLoS ONE)
Existing research on EFL learners' attitudes towards English language textbooks primarily investigates metaphors at the level of mental spaces, limiting insights into embodied cognition and experience. This study extends the analysis of metaphors to a more schematic level of domains/frames. We analyzed 163 metaphors from 123 Chinese university students' perceptions of English language textbooks under the guidance of Conceptual Metaphor Theory and the meta-functions of metaphors in language education. Findings reveal textbooks' three primary roles in learning English as i) a guide in a journey, ii) a cornerstone of a building, and iii) an appetizer in eating. The Chi-Square Test of Independence showed a moderate association between metaphor sources and emotional valence, with nature and container metaphors associated with negative evaluations. The combination of discourse analysis and statistical analysis highlights learners' physical and emotional engagement with English language textbooks. Pedagogical implications are discussed.